1999
DOI: 10.1007/bf02461358
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of sequential elements of bimanual behavior in the neuronal activity of the neostriatum in monkeys

Abstract: Neuron spike activity was recorded in the putamen of monkeys trained to perform bimanual operant behavior consisting of nine separate steps. Neuronal reactions were present at all steps: in 52-62% of cases during movement, and in 27-36% of cases during responses to the trigger and conditioned signals and as the monkeys decided which was the working hand. The proportion of inhibitory responses to the trigger stimulus was 9%, while inhibitory reactions accounted for 68% of reactions during hand movement in respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Orlov et al 17) recorded neuron spike activity in the putamen of monkeys trained to perform bimanual operant behavior consisting of nine separate steps and suggested the role of the putamen as neuronal reaction of complex operant behaviors. Also in our study, we found bilateral putamen showed strong activation under all 3 conditions (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Orlov et al 17) recorded neuron spike activity in the putamen of monkeys trained to perform bimanual operant behavior consisting of nine separate steps and suggested the role of the putamen as neuronal reaction of complex operant behaviors. Also in our study, we found bilateral putamen showed strong activation under all 3 conditions (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, deficits observed may be an indirect effect caused by disruption of the cortical network. Recent evidence of single unit activity specific to bimanual movements (Orlov et al, 1999;Wannier et al, 2002) might be considered a more direct indication the the basal ganglia play a role in the coordination of bimanual movements. Additionally, because neurosurgical techniques are often used to treat Parkinson's, electrophysiological evidence from human beings is also available.…”
Section: Which Brain Areas Are Involved In Bimanual Coordination?mentioning
confidence: 99%